The Transformation of Local Actors in the Globalization Process - Mahmut Mert Aslan; Hatice Erbay (LPPM Stikosa - AWS, 2023)
It is known that the dizzying development of mass communication technologies has transformed the people of the world into a global family. When it comes to globalization, it is a fact that the powerful actors ruthlessly swallow the local ones, and the discourses that everything local is erased hold a larger place in the memories; however, the erosion of local elements should not be considered as an absolute negative situation. In this context, all local actors, from local businesses operating in different sectors to primitive cultural groups isolated from the world, have gained worldwide advertising and promotion opportunities with globalization. From this point of view, it can be said that the fact that the local actors have the opportunity to promote, share and cooperate on a global scale is more meaningful than the fact that the global ones have become a more dominant power in the world. Concepts such as local business”,“ local newspaper and “local television channel” are no longer valid. There seems to be little place for the concept of “local” in the world, thanks to globalization. It should be added that the globalization of the local actors also includes the meaning of transferring some features from the global ones and evolving towards them. This study was carried out with the literature review method and aims to shed light on the direction of change of local actors in the globalization process.